2017
DOI: 10.1108/jopp-17-01-2017-b001
|View full text |Cite
|
Sign up to set email alerts
|

The role of training in dismantling barriers to sme participation in public procurement

Abstract: This paper examines entry barriers to involvement in public procurement of small and medium-sized enterprises and the role of training in dismantling those barriers. We find that firms' perceptions of barriers are of five main types. Regression analysis shows that a lack of ongoing training is associated with SMEs' perceptions of resource constraints and practical skills that hinder their participation in public procurement. We also observe a positive connection between a positive attitude toward training and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 32 publications
3
51
0
7
Order By: Relevance
“…Studies show that firm size (Flynn et al., 2015; Karjalainen and Kemppainen, 2008; Pickernell et al., 2011; Reijonen et al., 2016; Tammi et al., 2014) and age (Pickernell et al., 2013) are positively associated with supplying to the public sector. Further, SMEs’ tendering capabilities have been shown to improve their participation rate in public procurement (Flynn and Davis, 2016), and a lack of ongoing training is found to be associated with perceptions of resource constraints hindering SME participation in public procurement, while a positive attitude towards training is positively connected to participating in public procurement (Saastamoinen et al., 2017). It has also been shown that SMEs differ in their focus regarding the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that firm size (Flynn et al., 2015; Karjalainen and Kemppainen, 2008; Pickernell et al., 2011; Reijonen et al., 2016; Tammi et al., 2014) and age (Pickernell et al., 2013) are positively associated with supplying to the public sector. Further, SMEs’ tendering capabilities have been shown to improve their participation rate in public procurement (Flynn and Davis, 2016), and a lack of ongoing training is found to be associated with perceptions of resource constraints hindering SME participation in public procurement, while a positive attitude towards training is positively connected to participating in public procurement (Saastamoinen et al., 2017). It has also been shown that SMEs differ in their focus regarding the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have reported barriers hampering access of SMEs to public procurement. Saastamoinen et al (2017) identified five main variants of barriers to participation in public procurement. These are: a lack of resources, the problematic procurement processes which are related to matters such as policy, procurement organisation and culture, contract requirements and the tendering process, a lack of practical skills, a lack of awareness of public procurement, and a lack of skilled workers and partners.…”
Section: Barriers To Smes' Participation In Public Procurementmentioning
confidence: 99%
“…Other researchers added that these measures can either be regulated by legislation (McKevitt & Davis, 2015) or application of e-procurement (Fernandes & Vieira, 2015). Saastamoinen et al (2017) examined the role of training in dismantling the barriers of SMEs' participation in public procurement. A similar research was conducted by Egeberg (2016) to assess the suitability and implication of lot divisions in promoting SMEs' participation in public procurement.…”
Section: 10 Introductionmentioning
confidence: 99%
“…The evidence shows that firm size (Flynn et al, 2015;Karjalainen & Kemppainen, 2008;Pickernell et al, 2011;Reijonen et al, 2014;Tammi et al, 2014) and age (Pickernell et al, 2013) are positively associated with supplying to the public sector. In addition, it has been shown that competences which SMEs' display improve their participation rate in public procurement (Flynn & Davis, 2016), and that a shortage of training is associated with perceptions of resource constraints which in turn hinder SMEs participation in public procurement whereas an affirmative attitude towards training is positively associated with it (Saastamoinen et al, 2017). SMEs also differ in their focus regarding the public sector customer.…”
Section: Introductionmentioning
confidence: 99%